2017
DOI: 10.1007/s40843-016-5160-9
|View full text |Cite
|
Sign up to set email alerts
|

Production of yellow-emitting carbon quantum dots from fullerene carbon soot

Abstract: Carbon quantum dots (CQDs) have emerged as a new generation of photoluminescent nanomaterials with wide applications. Among the various synthetic routes for CQDs, the acid-refluxing method, which belongs to the group of "top-down" methods, offers the advantage of large-scale production of CQDs and uses cheap and abundantly available starting materials. In this study, we evaluated the potential of fullerene carbon soot (FCS), a by-product obtained during the synthesis of fullerene, as the starting material for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 60 publications
0
39
0
Order By: Relevance
“…Acid oxidation treatment have been widely used to exfoliate and decompose bulk carbon into nanoparticles, and simultaneously introduce hydrophilic groups, e.g., hydroxyl group or carboxyl group on the surface thereof to obtain CQDs (Shen and Xia, 2014; Zhang et al, 2017b), which could significantly improve the water solubility and fluorescence characteristics. In 2014, Yang et al (2014) reported a large-scale synthesis of heteroatom-doped CQDs via acid oxidation, followed by hydrothermal reduction.…”
Section: Synthetic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acid oxidation treatment have been widely used to exfoliate and decompose bulk carbon into nanoparticles, and simultaneously introduce hydrophilic groups, e.g., hydroxyl group or carboxyl group on the surface thereof to obtain CQDs (Shen and Xia, 2014; Zhang et al, 2017b), which could significantly improve the water solubility and fluorescence characteristics. In 2014, Yang et al (2014) reported a large-scale synthesis of heteroatom-doped CQDs via acid oxidation, followed by hydrothermal reduction.…”
Section: Synthetic Methodsmentioning
confidence: 99%
“…The variation of particle size and PL emission can be reflected from the broad and excitation-dependent PL emission spectrum (Sun et al, 2006). Zhang et al (2017b) studied the emission behaviors of CQDs under an irradiation at 470 nm wavelength with various concentrations. It was found that the PL strength of the CQDs solution first increased and then decreased as the concentration increased.…”
Section: Physical and Chemical Propertiesmentioning
confidence: 99%
“…Moreover, other examinations revealed that the CQDs have been strongly photostable in the broad pH-range and showed appropriate resistance in the ionic strength and lengthy UV irradiation which in turn increases their usage potential in undesirable conditions. 42 2.1.2. Bottom-up methods 2.1.2.1.…”
Section: Synthesis Of Cqdsmentioning
confidence: 99%
“…The PL emission changes due to particle size can be reflected in a broad excitation-dependent PL emission spectrum [24]. By studying the emission behavior of CQD at various concentrations at 470 nm, Zhang et al [25] reported that an increase in the concentration of the CQD solution led to an initial increase followed by a decrease in its PL intensity.…”
Section: Introductionmentioning
confidence: 99%